Matrix stiffness regulates SMC functions via TGF-β signaling pathway. (November 2019) - Tian, Baoxiang; Ding, Xili; Song, Yang; Chen, Weicong; Liang, Jiaqi; Yang, Li; Fan, Yubo; Li, Song; Zhou, Yue
Abstract: The stiffness change of the vessel wall is involved in many pathological processes of the blood vessel. However, how stiffness changes regulate vascular cell phenotype is not well understood. In this study, we investigated the effects of matrix stiffness on the phenotype and functions of vascular smooth muscle cells (SMCs). SMCs were cultured on the matrices with the stiffness between 1 and 100 kPa. The expression of contractile markers calponin-1 (CNN1) and smoothelin (SMTN) increased with stiffness; in contrast, the expression of synthetic markers osteopontin (OPN) and epiregulin (EREG) were the highest on the soft surface (1 kPa). In addition, matrix metalloproteinase 2 (MMP-2) was significantly upregulated on 1-kPa surface. Consistently, the stiffness of atherosclerotic lesions in human arteries decreased by up to 10 folds compared to normal area (>40 kPa), which was accompanied by a decrease of CNN1 expression and collagen content and an increase of OPN and MMP-2 in the area of lipid deposition. Furthermore, the phosphorylation of Smad2/3 increased with matrix stiffness; when TGF-β signaling pathway was inhibited, the stiffness effects on the SMCs were reversed. Our findings suggest that matrix stiffness regulates SMC phenotype and matrix remodeling through TGF-β signal pathway. This study unravels a mechanobiological mechanism in vascular remodeling, and will help us develop strategies for vascular tissue engineering, disease modeling and therapies.